2014
DOI: 10.1016/j.bpj.2014.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Coupling in PDE:PKA Complexes Promotes Resetting of Mammalian cAMP Signaling

Abstract: Cyclic 3'5' adenosine monophosphate (cAMP)-dependent-protein kinase (PKA) signaling is a fundamental regulatory pathway for mediating cellular responses to hormonal stimuli. The pathway is activated by high-affinity association of cAMP with the regulatory subunit of PKA and signal termination is achieved upon cAMP dissociation from PKA. Although steps in the activation phase are well understood, little is known on how signal termination/resetting occurs. Due to the high affinity of cAMP to PKA (KD ∼ low nM), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 78 publications
1
69
0
Order By: Relevance
“…Recently, Anand and coworkers (37,38) reported that phosphodiesterases (PDEs) can bind to and catalyze cAMP release from PKA RIα. The ligands are channeled from the tandem CBDs to the active sites of a PDE dimer and then hydrolyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Anand and coworkers (37,38) reported that phosphodiesterases (PDEs) can bind to and catalyze cAMP release from PKA RIα. The ligands are channeled from the tandem CBDs to the active sites of a PDE dimer and then hydrolyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were injected onto a nano-UPLC HDX sample manager (Waters, Milford, MA) as described in Wales et al (39). Online immobilized pepsin digestion and reverse phase liquid chromatography were carried out as previously described in Krishnamurthy et al (27). Peptides separated from previous liquid chromatography were subsequently sprayed onto a SYNAPT G2-Si mass spectrometer (Waters) acquiring in MS E mode.…”
Section: Amide Hydrogen/deuterium Exchange Mass Spectrometrymentioning
confidence: 99%
“…PDEs, enzymes responsible for catalyzing hydrolysis of cAMP to 5 0 AMP, initiate the termination phase of the cAMP signaling pathway by forming direct interactions with the cyclic-nucleotide-binding (CNB) pocket domains of PKA R-subunit and hydrolyzing the bound cAMP ( Fig. 1 A) (19,27). The R-subunit of D. discoideum (henceforth referred to as R D ) differs from its mammalian homologs in being monomeric, and lacks an N-terminal dimerization domain, but contains two canonical cyclic AMP binding sites in two distinct domains, CNB domains A and B (denoted CNB:A and CNB:B) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations